Robust finite-time integral terminal sliding mode control design for maximum power extraction of PMSG-based standalone wind energy system - Hua, Lyu-Guang; Ali, Ammar; Ullah, Safeer; Hafeez, Ghulam; Zaidi, Monji Mohamed; Jun, Liu Jun (Frontiers in Energy Research, 2023)
This paper introduces a novel control strategy called Finite-time Integral Terminal Sliding Mode Control (FITSMC), explicitly designed for a permanent-magnet synchronous generator (PMSG)-based standalone Wind Energy Conversion System (WECS). The primary objective of the FITSMC strategy is to regulate the operation of the wind turbine efficiently and maximize power extraction from the WECS. To achieve this, the system is driven onto a sliding surface within a predefined terminal time, ensuring rapid convergence and overall stability. An important advantage of the FITSMC strategy is its ability to maintain a standalone wind power system close to the maximum power point, even under varying wind conditions and load changes. In addition, the controller demonstrates robustness against uncertainties and disturbances, making it highly suitable for real-world applications. Extensive simulations and analyses have been conducted to validate the effectiveness of the proposed FITSMC. The results show a superior control performance compared to traditional methods. Consequently, the FITSMC strategy represents a promising advancement in control techniques for standalone wind power systems, providing an efficient and reliable approach for harnessing power from wind energy.